The The Role of Financial Performance in Mediating the Relationship of CEO Narcissism and Free Cash Flow on Earnings Management - Andini Melinia Sari; Susi Retna Cahyaningtyas (Cita Konsultindo Research Center, 2024)
Users of financial statements use earnings as one of the important benchmarks that attract external attention when assessing company performance. Some literature on corporate governance has focused on how CEO characteristics influence decisions, including those in earnings management. This study aims to test whether a narcissistic CEO and high free cash flow will motivate management to perform earnings management with financial performance as a mediating variable. This type of research is explanatory, using purposive sampling techniques in selecting samples. The samples in this study were 44 financial or banking service companies that have been listed on the Indonesia Stock Exchange for the period 2020–2022, for a total of 132 observations. The results showed that CEO narcissism can affect earnings management practices, while free cash flow does not affect earnings management. Furthermore, CEO narcissism affects financial performance, while free cash flow cannot affect financial performance. Then, financial performance has no effect on earnings management, and financial performance can mediate the relationship between CEO narcissism and earnings management but is unable to mediate the effect between free cash flow and earnings management.